APPLICATION OF ADAPTIVE LEARNING IN IMPROVING THE LEARNING OUTCOMES OF JUNIOR HIGH SCHOOL STUDENTS - Choi Sun Hui (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2026)
Adaptive learning technologies have emerged as a promising solution to address the diverse learning needs of students, offering personalized educational experiences that can improve learning outcomes. In the context of junior high school education, where students possess varied academic abilities and learning styles, adaptive learning can be particularly effective in promoting engagement and academic success. This study investigates the application of adaptive learning in improving the learning outcomes of junior high school students, focusing on its impact on both academic performance and student engagement. A mixed-methods research design was employed, combining quantitative assessments of student performance with qualitative surveys on student engagement. The study involved 200 junior high school students who participated in adaptive learning programs in subjects such as mathematics and science. The results indicate that students who engaged with adaptive learning tools demonstrated a significant improvement in academic performance, with an average increase of 18.5% in test scores. Additionally, students reported higher levels of engagement and motivation in learning activities. This study concludes that the implementation of adaptive learning systems can significantly improve learning outcomes by providing personalized, data-driven support tailored to individual student needs. Educational institutions are encouraged to integrate adaptive learning technologies to enhance student success.